STUDY OF MATERNAL MORTALITY RATE AT A TERTIARY CARE TEACHING HOSPITAL IN NORTHERN INDIA: A RETROSPECTIVE STUDY - Gupta Pooja; Chandra Subrat; Habib Mariya (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: All pregnant women are at risk of obstetrical complications and most of these occur during labour and delivery that lead to maternal morbidity and mortality. Maternal death has serious implications on the family, the society and the nation. Maternal Mortality Ratio (MMR) is a very sensitive index that reflects the quality of reproductive care provided to the pregnant women. Objectives: To assess the maternal mortality ratio and the causes of maternal death over a period of one year at a tertiary care teaching hospital of India. Methods: A retrospective hospital-based study of 25 maternal deaths over a period of 1 year.